1989
DOI: 10.1128/jb.171.9.4799-4806.1989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular analyses of the gene encoding staphylococcal enterotoxin D

Abstract: The gene (entD) encoding staphylococcal enterotoxin D (SED) has been located on a 27.6-kilobase penicillinase plasmid designated pIB485. This plasmid was present in all SED-producing strains tested. The entD gene was cloned on a 2.0-kilobase DNA fragment and was expressed in Escherichia coli. Sequence analysis of this fragment revealed an open reading frame that encoded a 258-amino-acid protein that possessed a 30-amino-acid signal peptide. The 228-amino-acid mature polypeptide had a molecular weight of 26,360… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
137
1
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(143 citation statements)
references
References 46 publications
(31 reference statements)
2
137
1
1
Order By: Relevance
“…The gene for SEA is bacteriophage encoded (Betley and Mekalanos, 1985). In contrast, the gene for SED is encoded by an antibiotic-resistance plasmid (Bayles and Iandolo, 1989). The sequence of the gene that encodes SEJ is on the same plasmid as that for SED (Zhang et al, 1998).…”
Section: Uuxtaaislsigmentioning
confidence: 99%
“…The gene for SEA is bacteriophage encoded (Betley and Mekalanos, 1985). In contrast, the gene for SED is encoded by an antibiotic-resistance plasmid (Bayles and Iandolo, 1989). The sequence of the gene that encodes SEJ is on the same plasmid as that for SED (Zhang et al, 1998).…”
Section: Uuxtaaislsigmentioning
confidence: 99%
“…The multiple spots of toxins may be generated in a similar way by the action of own proteases, although we have had no evidence yet. A potent virulence factor, TSST-1, was identified as spot F straight down from the major SEC 3 (45). Collagen adhesin of MF330 was closer to the latter one.…”
Section: Identification Of Exoprotein Spotsmentioning
confidence: 99%
“…The first group of exoproteins are alpha-toxin (14), beta-hemolysin (47), gammahemolysin (46), delta-hemolysin (20), and phospholipase C (9). The second group are toxic shock syndrome toxin-1 (TSST-1) (29), enterotoxins (3,4,8,15,22,52), protein A (34), and others (6,31,32,50,53), and the third group contains clumping factor (37) and others (7,12,23,45). More than 30 of these exoproteins that are significantly linked to pathogenesis have been purified to homogeneity, and the genes encoding these exoproteins have been cloned and sequenced (5,48 Abstract: We applied two-dimensional gel electrophoresis (2-DE) to the total exoproteins secreted from pathogenic MRSA strains and identified major protein spots by N-terminal amino acid sequence analysis.…”
mentioning
confidence: 99%
“…Other investigators have demonstrated the importance of global regulators in controlling the expression of several staphylococcal extracellular proteins [8][9][10][11][12][13][14][15][16][17][18][19][20]. Two of these regulatory elements, the accessory gene regulator (Agr) and the staphylococcal accessory regulator (Sar), control expression of exoproteins by transcriptional control [ 13,141.…”
Section: Introductionmentioning
confidence: 99%